2011
DOI: 10.1002/ejoc.201001443
|View full text |Cite
|
Sign up to set email alerts
|

Indium‐Mediated Allenylation of Aldehydes and Its Application in Carbohydrate Chemistry: Efficient Synthesis of D‐Ribulose and 1‐Deoxy‐D‐ribulose

Abstract: A two-step reaction sequence starting with the indium-mediated allenylation of aldehydes with 4-bromo-2-butyn-1-ols and subsequent ozonolysis of the resulting allenylic product was developed to generate a variety of dihydroxyacetone derivatives. The regioselectivity of the indium-promoted C-C bond-forming reaction can be manipulated through hydroxy protecting groups on 4-bromo-2-butyn-1-ol, yielding either

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…Although 8 had been prepared earlier by our group,[3i] we developed in this work a more convenient route starting from the known propargyl bromide 17 (Scheme ) . Hydroxymethylation of 17 by treatment with tin powder and paraformaldehyde in the presence of lithium iodide gave allene 18 and a small amount of alkyne 19 , which were easily separable , . From 18 , the desired allenyl bromide 8 was obtained in 70 % through the action of phosphorus tribromide.…”
Section: Resultsmentioning
confidence: 99%
“…Although 8 had been prepared earlier by our group,[3i] we developed in this work a more convenient route starting from the known propargyl bromide 17 (Scheme ) . Hydroxymethylation of 17 by treatment with tin powder and paraformaldehyde in the presence of lithium iodide gave allene 18 and a small amount of alkyne 19 , which were easily separable , . From 18 , the desired allenyl bromide 8 was obtained in 70 % through the action of phosphorus tribromide.…”
Section: Resultsmentioning
confidence: 99%
“…Additional contributions were reported in the literature by Paquette and co-workers concerning indium-mediated reactions in water and their stereochemistry [67]. Based on these findings this elongation method has been established as reliable and efficient approach in carbohydrate chemistry, shown by many examples reported in the literature [812]. Thus far, this method has been applied to monosaccharides [1314].…”
Section: Introductionmentioning
confidence: 95%
“…In 2011, Schmid and co-workers showed that different ratios of allenols 298 and homopropargylic alcohols 299 could be obtained in the In-mediated Barbier-type addition of 4-hydroxypropargyl bromides 297 to D-glyceraldehyde acetonide, depending on the hydroxy protecting group type used (Scheme 80). 50 It was found that the application of substrates containing OMe, OAc, OCbz, and especially unprotected hydroxy groups, capable of coordinating to the indium center in the generated four-and six-membered chelated allenylindiums 300 and 302, respectively, led to an increase in the homopropargylic alcohol 299 ratio. On the other hand, the use of precursors bearing a hydroxy protected with the more bulky Bn and TBDPS groups, as well as propargyl bromides with no hydroxy group or with this functionality too distant to coordinate to the indium atom, delivered the regioisomeric allenols 298 in predominance as the result of participation of the standard open-chain, non-chelated propargylindium 301.…”
Section: Additions Of Chelated Allenylindiumsmentioning
confidence: 99%
“…As a demonstration of the applicability of the developed method in asymmetric synthesis, straightforward approaches to D-ribulose and 1-deoxy-D-ribulose were executed, starting from D-glyceraldehyde acetonide and bromides 297a and 297g, respectively (Scheme 81). 50 In both cases, a sequence of transformations including highly regio-…”
Section: Additions Of Chelated Allenylindiumsmentioning
confidence: 99%